Calidad culinaria de 13 líneas avanzadas de arroz (Oryza sativa L.), en comparación con la variedad SFL-011 adaptada en las zonas arroceras del Ecuador - Cruz Santana, Andrea Belén (2022)
In this study, an analysis of the culinary quality of 13 advanced lines of rice (Oryza sativa L.) was carried out, in comparison with the variety SFL-011 adapted in the rice-growing areas of Ecuador, as well as other research related to sensory evaluations of rice. other varieties of rice, with the aim of knowing the variables of degree of acceptability, smell, grain separation, flavor, color and texture, determining the lines with the best characteristics for consumers. As a result of this research, in the degree of acceptability, line 7 with the parameter "I like it a lot" obtained 63%, line 18 with 60% and line 19 with 57%, while in the SFL-011 variety of Daule got 50%. In the smell variable "rice" in line 17 it reached 70%, line 33 with 57% and line 4 with 50%, "popcorn" reached 50% in line 9, while in the SFL variety -011 “rice” obtained 57% and “popcorn” in the town of Yaguachi reached 30%. Regarding the degree of grain separation, line 4 expressed "moderately sticky" with 77%, in this parameter most of the lines were qualified as "sticky" and "moderately sticky", in the SFL-011 variety it was obtained "separate" and "moderately separated" was the most chosen by the sensory panel for the 4 locations. In the flavor variable, the "rice" parameter was the most preferred in almost all the lines, including the SFL-011 variety of the 4 locations with more than 50%. Regarding the color variable, the "white" parameter was obtained in line 33 with 57%, lines 4 and 12 with 43%, the "bone" color in lines 4, 10, and 19 with 37%, while, in the variety SFL-011 qualified as "white" in the 4 locations with a range of 57-73%. In texture, the parameter "sticky" line 4 with 87%, in most lines this parameter of 30 and 67%, in the variety SFL-011 it was "hard" between 30 and 67% in the four rice localities.